Neonatal Uterine Bleedings: An Ignored Sign but a Possible Cause of Early-Onset Endometriosis – A Systematic Review - Judith Dekker; Isabelle Hooijer; Johannes C.F. Ket; Aleksandra Vejnović; Giuseppe Benagiano; Ivo Brosens; Velja Mijatovic (Biomedicine Hub, 2021)
Objective: Based on the hypothesis that neonatal uterine bleedings (NUB), occurring mostly in the first week after birth, could represent a pathogenetic mechanism for early-onset endometriosis, this systematic review (SR) was undertaken to evaluate the prevalence and screening strategies used to assess and quantify NUB. Design: Both a SR and a sample literature search in PubMed and Embase were conducted to gather information on NUB prevalence and screening techniques. This was performed by an information specialist. Only full-text articles regarding the assessment of NUB in neonates in the first 2 weeks after birth were included. No limit on language or publication data was used. Materials and Methods: The SR was registered in PROSPERO (CRD42019138121). Data was first assessed for eligibility on title and abstract by 2 blinded review authors. Any disagreements were discussed with a third reviewer if necessary. Subsequently, full-text articles were read and assessed for quality using the Cochrane Collaboration Handbook. Results: Out of 1,988 articles in the systematic search, 10 relevant articles were selected, of which 8 were identified through the systematic search and 2 were found through other sources. The sample search of 4,445 articles did not bring up relevant articles. Results were not comparable due to the heterogeneity of screening techniques, although data showed consensus. The prevalence of visible bleeding ranged from 3.3 to 53.8% and the prevalence of occult bleeding from 25.4 to 96.7%. The occurrence was the highest between the 3rd and 7th day postpartum (PP) and the bleeding lasted for 3–4 days on average. Various screening techniques for detecting NUB were found in the literature, including the use of hemoglobin detection devices (such as Hemastix) in the vaginal vestibulum, comparison of diapers with stains of known volume, colposcopy, and ultrasonography. Conclusion: The reported prevalence of NUB varies considerably, with a consistent occurrence between the 3rd and the 7th day PP. Literature to assess NUB is dated. The techniques are poorly described and heterogeneous. Future research should focus on prospective cohort studies in order to attempt to correlate NUB cases to (early-onset) endometriosis.